Cryoconite Hole Location in East-Antarctic Untersee Oasis Shapes Physical and Biological Diversity - Weisleitner, Klemens; Perras, Alexandra Kristin; Unterberger, Seraphin Hubert; Moissl-Eichinger, Christine; Andersen, Dale T.; Sattler, Birgit (Frontiers in Microbiology, 2020)
Antarctic cryoconite holes (CHs) are mostly perennially ice-lidded and sediment-filled depressions that constitute important features on glaciers and ice sheets. Once being hydrologically connected, these microbially dominated mini-ecosystems provide nutrients and biota for downstream environments. For example, the East Antarctic Anuchin Glacier gradually melts into the adjacent perennially ice-covered Lake Untersee, and CH biota from this glacier contribute up to one third of the community composition in benthic microbial mats within the lake. However, biogeochemical features of these CHs and associated spatial patterns across the glacier are still unknown. Here we hypothesized about the CH minerogenic composition between the different sources such as the medial moraine and other zones. Further, we assumed that the depth of the CH mirrors the community composition, organic matter content and would support productivity. Here we show that both microbial communities and biogeochemical parameters in CHs were significantly different between the medial moraine and the glacier terminus. Variations in microbial community composition are the result of factors such as depth, diameter, organic matter, total carbon, particle size and mineral diversity. More than 90% of all ribosomal sequence variants (RSV) reads were classified as Proteobacteria, Cyanobacteria, Bacteroidetes, Actinobacteria, and Acidobacteria. Archaea were detected in 85% of all samples and exclusively belonged to the classes Halobacteria, Methanomicrobia and Thermoplasmata. The core microbiome for bacteria comprised 30 RSVs affiliated with Cyanobacteria, Bacteroidetes, Actinobacteria and Proteobacteria. The archaeal fraction of the core microbiome consisted of three RSVs belonging to unknown genera of Methanomicrobiales and Thermoplasmatales and the genus Rice_Cluster_I (Methanocellales). Further, mean bacterial carbon production in cryoconite was exceptionally low and similar rates have not been reported elsewhere. However, bacterial carbon production insignificantly trended towards higher rates in shallow CHs and did not seem to be supported by accumulation of organic matter and nutrients, respectively, in deeper holes. Organic matter fractions were significantly higher at the glacier terminus. We conclude that wind-blown material originating south and southeast of the Anuchin Glacier and deposits from a nunatak are assumed to be local inoculation sources. Moreover, we suggest that CH location shapes physical and biological diversity.